Analysis of home industry working capital needs "MSMES Ida Ayu" Pekon Pringsewu: Wagiyo, A14 - Wagiyo, Wagiyo; Purwanto, Purwanto; Pasya, Dhel Juni; Arifin, Arifin (Jurnal Mantik, 2024)
With the growing development of MSMEs in Indonesia today, so that MSMEs are more effective in increasing capacity, for operations in running a business require funding or working capital both for daily needs and for the long term, where capital is an obstacle faced by MSMEs, especially for MSMEs that are located far from the reach of banking institutions. With a cash turnover rate of 76.86 days; and receivables turnover of 64.21 days; which is followed by an inventory of 64.21 days, thus it is known that the length of working capital turnover is 161.55 days, with a working capital turnover for 1 year (360) days is 2.23 times, with sales of Rp. 1,251,200,000,- divided by 2.23 times the required capital of Rp.561,468,726,- while the prediction of the sales level will increase by 18%, while the available working capital is Rp. 560,361,000,- so that MSMES IDA AYU needs to get additional funds for additional Karja Capital of Rp. 102,172,096